(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The prevalence of exam malpractice poses a significant challenge to educational systems worldwide. To devise effective countermeasures, it’s crucial to comprehend the underlying factors that drive such misconduct. This research focuses on moral disengagement, a psychological process that permits individuals to partake in unethical actions without remorse as a potential contributor to exam malpractice among River State, Nigeria university students. Through a survey of 337 undergraduates across three public tertiary institutions, the study employed both descriptive and inferential statistical methods for data evaluation. Results indicate a substantial effect of moral disengagement on the propensity for exam malpractice. Notably, a moderate positive correlation was observed between moral detachment and instances of cheating, with a correlation coefficient, r (235) = .44 ) and a significance level of ( p < .001 ). Furthermore, moral disengagement accounted for 12.6% of the variance in cheating behaviors. These insights bear significant implications for the advancement of educational policies and institutional practices.